The Implementation of Language Exchange on The Hellotalk App to Practice the Speaking Skills of Students in The Mandarin Language Education Study Program State University of Malang - Rizki Amalia; Iwa Sobara; Karina Fefi Laksana Sakti (Universitas Negeri Malang, 2024)
This study evaluates the implementation of Language Exchange through the HelloTalk app to enhance the speaking skills of Mandarin Language Education students at State University of Malang, Class of 2022. In the era of globalization, Mandarin language skills are becoming increasingly important. A descriptive qualitative method was used to collect data through observation, questionnaires, and interviews. The results show that language exchange via HelloTalk positively impacts students' confidence and motivation in speaking Mandarin. Students feel more comfortable communicating with native speakers and gain a more interactive learning experience. Although some challenges relate to app feature access, most students recommend its use. This study suggests integrating Language Exchange with apps like HelloTalk to boost students' confidence and motivation in Mandarin language learning. Future research is recommended to involve participants from more diverse backgrounds and explore the potential of language exchange in learning other languages.